PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH, BUDAYA SEKOLAH DAN MOTIVASI KERJA TERHADAP KOMITMEN KERJA GURU SD DI KABUPATEN ACEH BARAT - Suhelmi Suhelmi; Najamuddin Najamuddin; Marwan Marwan (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
The aims of this research are (1) To determine the influence of the school principal's democratic leadership style on the work commitment of Samatiga Core 1 Primary School Teachers in West Aceh Regency, (2) To determine the influence of school culture on the work commitment of Samatiga Core 1 Elementary School Teachers in Aceh Regency. West, (3) To determine the influence of work motivation on the work commitment of Core 1 Elementary School Teachers in Samatiga in West Aceh Regency, and (4) To determine the influence of the principal's democratic leadership style, school culture and work motivation on the work motivation of Core 1 Elementary School Teachers of Samatiga. in West Aceh Regency. This research uses a quantitative method with a descriptive approach, a population of 75 people, a sample of 75 people, a simple random sampling technique using Sugiyono's sampling technique. The data collection technique was carried out using a Likert scale questionnaire and multiple linear regression data processing techniques. The research findings were partially obtained, (1) the principal's democratic leadership style did not have a positive influence on teacher work commitment with a coefficient of 0.072 or 7.2% (in percentage), hypothesis testing produced a calculated T value of 1.828 which was smaller than the T value table 1,993. This shows that the principal's democratic leadership style variable has no effect on teacher work commitment. (2) School culture does not have a positive influence on teacher work commitment with a coefficient of 0.365 or 36.5% (in percentage). Hypothesis testing produces a calculated T value of 0.912 which is smaller than the T table value of 1.993. (3) work motivation has a positive influence on teacher work commitment with a coefficient of 0.009 or 0.9% (in percentage), hypothesis testing produces a calculated T value of 2.706 which is greater than the T table value of 1.993. Meanwhile, simultaneously it was found that the principal's democratic leadership style, school culture and work motivation had a positive influence on teacher work commitment with a constant value of 25,658. The findings in this research have practical implications, namely the principal's democratic leadership style, school culture and work motivation have implications for the work commitment of Samatiga Primary 1 Elementary School teachers in West Aceh Regency. Advice to all school principals is that the implementation of the principal's democratic leadership style should be given more attention and carried out with full responsibility, and the output is the realization of the work commitment of the Samatiga Core 1 Elementary School teachers in West Aceh Regency, in this way the teacher's work commitment will increase and be maximized. Motivation The work of a teacher must also be owned and maintained by every teacher, and school culture also needs to be preserved and implemented with a full sense of responsibility, so that it is hoped that it can form a disciplined teacher personality. so that the school's vision and mission targets can be easily achieved, and have an impact on improving the quality of education nationally.